Sialokinin in mosquito saliva shifts human immune responses towards intracellular pathogens - Jennifer L. Spencer Clinton; Megan B. Vogt; Alexander R. Kneubehl; Brianne M. Hibl; Silke Paust; Rebecca Rico-Hesse (Public Library of Science (PLoS), 2023)
Mosquito saliva is a mix of numerous proteins that are injected into the skin while the mosquito searches for a blood meal. While mosquito saliva is known to be immunogenic, the salivary components driving these immune responses, as well as the types of immune responses that occur, are not well characterized. We investigated the effects of one potential immunomodulatory mosquito saliva protein, sialokinin, on the human immune response. We used flow cytometry to compare human immune cell populations between humanized mice bitten by sialokinin knockout mosquitoes or injected with sialokinin, and compared them to those bitten by wild-type mosquitoes, unbitten, or saline-injected control mice. Humanized mice received 4 mosquito bites or a single injection, were euthanized after 7 days, and skin, spleen, bone marrow, and blood were harvested for immune cell profiling. Our results show that bites from sialokinin knockout mosquitoes induced monocyte and macrophage populations in the skin, blood, bone marrow, and spleens, and primarily affected CD11c- cell populations. Other increased immune cells included plasmacytoid dendritic cells in the blood, natural killer cells in the skin and blood, and CD4+ T cells in all samples analyzed. Conversely, we observed that mice bitten with sialokinin knockout mosquitoes had decreased NKT cell populations in the skin, and fewer B cells in the blood, spleen, and bone marrow. Taken together, we demonstrated that sialokinin knockout saliva induces elements of a TH1 cellular immune response, suggesting that the sialokinin peptide is inducing a TH2 cellular immune response during wild-type mosquito biting. These findings are an important step towards understanding how mosquito saliva modulates the human immune system and which components of saliva may be critical for arboviral infection. By identifying immunomodulatory salivary proteins, such as sialokinin, we can develop vaccines against mosquito saliva components and direct efforts towards blocking arboviral infections. Author summary Numerous studies have shown the effects of mosquito saliva proteins on the immune system of animals and humans with disease caused by mosquito-borne pathogens. We have previously described some of these effects in humanized mice (which contain specific human immune system cells and develop arboviral diseases similar to humans) infected by mosquito bite with dengue and chikungunya viruses. In this study, we show that humanized mice have altered cellular immune responses after they are bitten by uninfected mosquitoes lacking the sialokinin salivary protein. Our results suggest that sialokinin alone shifts mammalian immunity towards a TH2 response, away from the anti-viral, cell-mediated, and humoral responses that would protect against viruses included in the saliva. This is the first study of its kind, and it highlights how the effects of specific saliva components can be evaluated for human therapeutic intervention.